Analisis Curah Hujan Untuk Kekeringan Meteorologis Di Kabupaten Kulon Progo Tahun 2006-2015 - Mustaqim, Haris; Drs. H. Yuli Priyana, M.Si (2016)
Meteorological drought may adversely affect rice farmers due to lack of water in the supplier of its growth, resulting in a reduction in production and a decrease in the quality of rice. Kulon Progo Regency research areas by considering some circumstances. The purpose of this study namely 1) Analyze Shareable kekerigan prone areas in the area of Kulon Progo Regency historically from year 2006 to 2015; 2) To analyze the impact of drought on agriculture food (rice) in the area of Kulon Progo Regency; and 3) determine the classification of climatic zones as an alternative area of Kulon Progo Regency anticipate agricultural drought disaster. The method used is the method of indirect observation and interviews. Observation activities conducted to obtain secondary data is data of rainfall and agricultural production as well as the extent of the data from 2006 to 2015. Data rainfall drought index calculated each month using methods Standarized Precipitation Index. Comparative spatial analysis is used to distinguish the spatial variation of meteorological drought level of the processing of the maximum drought index each year, so the distribution of the data obtained in the form of spatial area using the Inverse Distance Weight and Thiessen polygon method for classification of agro-climatic zoning Oldeman. Spatial trend analysis used to answer to which direction (spatial orientation) a change in the space that occurs from the effects of drought. Qualitative Descriptive Analysis is used to explain and illustrate the impact of the drought on rice farming from the data comparison of agricultural productivity of rice with a drought index with the same period of the year. Unstructured interviews conducted on farmers affected by drought and District Agriculture Office Kulonprogro to support the updating of the data and the results of the processing performed related to agricultural production. Results show generally Kulon Progo Regency has a uniform climate conditions and do not have a history of fairly extreme drought. Months have the greatest possibility for the occurrence of drought is the month of May, June and December and drought prone regions potentially namely Sub Nanggulan, Compassionate, and Girimulyo. Kulonprogro region is divided into two zones, namely agro-climatic zones in the northern part C2 and C3 zone in the selatan.Pemerintah with the community of Kulon Progo Regency has made a good policy associated with the anticipation of drought with the implementation of an integrated irrigation system all of the fields in Kulon Progo Regency, so that the results showed precipitation is not influential factor in the productivity of rice.